STRUKTUR KOMIK STRIP DI AKUN INSTAGRAM KOMIK GRONTOL DAN KOSTUM KOMIK - Silviari, Ratih Ayu; Mulasih, Mulasih (Universitas Peradaban, 2024)
The aim of this research is to describe and analyze the structure of comics found in the comic strips on the Instagram accounts Komik Grontol and Kostum Komik. This type of research is qualitative. The research method used is descriptive. The data collection techniques used are reading, noting, and documentation techniques. The results of the study show the comic strip structure found in the comic strips on the Instagram accounts Komik Grontol and Kostum Komik. The character structure found is 26 characters in the comic strips on the Instagram accounts Komik Grontol and Kostum Komik. The plot structure found is 9 linear plots and 1 mixed plot in the comic strips on the Instagram accounts Komik Grontol and Kostum Komik. The theme and moral structure found is 8 themes and 11 morals in the comic strips on the Instagram accounts Komik Grontol and Kostum Komik. The structure of the comic strip in terms of images and language found is that the characters in the comics are depicted as humans, while the language aspect consists of narratives, words in thought balloons and speech balloons, as well as sound effects. Keywords: comic structure, comic strips, Instagram